An Examination of Methodological Approaches in Applied Technology Classrooms: A Reflective Perspective from Vocational and Training Educators - Borden Lanza, Yonathan Humberto; Lores Gómez, Beatriz; Usart Rodríguez, Mireia (RiiTE Revista interuniversitaria de investigación en Tecnología Educativa, 2024)
This research exposes the pertinent methodological considerations regarding digital competence for educators in Vocational Training Applied Technology classrooms. The study employs deductive thematic analysis, a well-established design recognised for effectiveness in examining and validating specific theoretical frameworks. To uphold the thematic analysis's rigour, it incorporates thorough preparation, systematic methodologies, and meticulous record-keeping, particularly when handling extensive datasets. Instruments were used for research in six vocational education and training (VET) institutions with Applied Technology Classrooms (ATCs) in Catalonia's Tarragona, Barcelona, and Lleida provinces. The study included interviews and focus groups with twenty-five participants, and two classes were observed after data collection was processed with the Turboscribe.ai application and uploaded to the ATLAS.ti system Version 24.1.1 for analysis of the participants' discourse. Participants have addressed integrating advanced technologies, including 3D printing, virtual reality, and laser cutting, into the educational framework of ATC as the pivotal seeker to transform and modernise vocational education. This strategic incorporation has the potential to revolutionise teaching methodologies, allowing students to engage in experiential learning and directly apply theoretical knowledge. However, some significant challenges have been identified: (1) the pressing need for VET teachers to improve their digital competencies. (2) Furthermore, there is a need to address the implementation of digital mentorship and training initiatives and the practical digital instructional skills of educators and their official certifications. (3) A frank methodological approach is needed to develop better actions in the ATCs.